Physics of the environment and climate - Guyot, Gérard (John Wiley & Sons, 1998)
Physics of the Environment and Climate brings together the basic concepts of thermodynamics, fluid mechanics, external geophysics, plant biology and ecology, which are important in the understanding of the complex global and climatological phenomena relating to the environment. Providing a single source for information previously found scattered among specialised books in physics, meteorology, climatology, ecophysiology and agronomy, this book provides a clear exposition of a wide-ranging subject.